Change of Fixed Allowance Wage System to Performance Incentive - Ma’ruf Okky Setiawan; Thea Farina; Nuraliyah Ali (Dinasti Research, 2025)
In the context of Indonesian labor law, this research looks at how the wage system changed from fixed allowances to performance incentives. This research aims to study the legal consequences of the change in Law Number 13 Year 2003 on Manpower, specifically Article 55, Article 92, Article 110, and Article 111 letter (b). Based on primary and secondary legal materials, this research uses a normative legal method with a qualitative descriptive approach.The results show that workers can experience negative impacts if fixed allowances are converted into performance incentives. This is especially true when calculating severance pay related to fixed allowances. Companies can review the wage structure under Article 92: however, this must be done with the involvement of workers, as stipulated by Article 110 and Article 111 letter (b). In addition, Article 55 confirms that employment agreements cannot be changed unilaterally without the consent of both parties. Analysis of case law shows that violations of these principles can lead to industrial relations conflicts. Therefore, it is important to ensure that changes to the wage system are made with worker involvement, transparency, and in compliance with applicable laws. This research concludes that stricter regulations and government supervision are needed to ensure that wage policy changes are fair and protect workers' rights, while creating harmonious industrial relations.